Grit and social responsibility in students with Education 4.0 and Learning and Service projects (Revista Innova Educación, 2024)
In this study, we aimed to evaluate the effectiveness of an enhanced Education 4.0 proposal incorporating Service Learning (SL) among university students. A quantitative research was conducted with a sample of 30 students from Universidad de Aconcagua (Chile) during the period from April to June 2024. Data were collected using questionnaires with sufficient validity and reliability; the first instrument assessed Grit on the 12-item Grit-O scale with scores ranging from 1 to 5, with 5 being the highest level, and the second instrument measured social responsibility from 1 to 6, with 6 as the maximum value. The results indicate that the use of Education 4.0 along with Service Learning showed a significant increase in social responsibility, rising from 4.96 to 5.37 (p
Keywords: Learning and Service; Education 4.0; university training; Grit; social responsibility